Energy efficient multi-tasking for edge computing using federated learning - Soni, Mukesh; Nayak, Nihar Ranjan; Kalra, Ashima; Degadwala, Sheshang; Singh, Nikhil Kumar; Singh, Shweta (International journal of pervasive computing and communications, 2024)
PurposeThe purpose of this paper is to improve the existing paradigm of edge computing to maintain a balanced energy usage.Design/methodology/approachThe new greedy algorithm is proposed to balance the energy consumption in edge computing.FindingsThe new greedy algorithm can balance energy more efficiently than the random approach by an average of 66.59 percent.Originality/valueThe results are shown in this paper which are better as compared to existing algorithms.